Nutritional Analysis of Three Commonly Consumed Varieties of Sorghum (Sorghum bicolor L.) in Bauchi State, Nigeria - Z.S. Mohammed; A.H. Mabudi; Y. Murtala; S. Jibrin; S. Sulaiman; J. Salihu (Journal of Applied Sciences and Environmental Management)
Three sorghum samples (yellow, red, and white sorghums) were analyzed for their proximate, vitamin (B1, B3, B6) and mineral element (Mg, Na, K, Ca, Fe, Zn, Cu and Mn) compositions. Vitamins and mineral compositions were determined using HPLC and AAS respectively. The results of the proximate analysis revealed that there was no significant difference (p ≤ 0.05) in the ash, crude fibre, crude protein and carbohydrate content of the three samples. The difference in the moisture and fat content were significant (p ≤ 0.05). The moisture content of white and red sorghum and white and yellow sorghums was significantly different (p ≤ 0.05) while the difference in the moisture of red and yellow sorghums was not significant (p ≤ 0.05). The fat content of white and red sorghum are significantly different (p ≤ 0.05) while the difference between the fat content of white and yellow and red and yellow sorghums were not significant (p ≤ 0.05). White sorghum has higher percentage of moisture and fat 11.90±0.36 & 9.26±1.81 respectively. Red sorghum has higher percentage of ash and protein 2.32±0.68 & 6.08±0.40 respectively. Yellow sorghum has higher percentage of fibre and carbohydrate 2.41±1.44 & 73.53±1.87 respectively. The HPLC vitamin analysis showed that sorghum has low vitamin B1 (thiamine), B3 (niacin), B6 (pyridoxine) content and did not meet the recommended dietary allowance of the world health organization, although red sorghum was richer in all the vitamins analyzed, followed by yellow sorghum and then white sorghum which has the lowest vitamin content. The AAS results for the mineral elements revealed that all the three sorghum varieties contains all the mineral elements analyzed except for white sorghum which does not show any trace of copper. Statistical analysis on the mineral elements of the three sorghum showed that there were no significant difference (p ≤ 0.05) in all the mineral elements analysed with respect to each of the samples except for calcium that showed a significant difference (p ≤ 0.05). The difference in the calcium content between white and red sorghum and red and yellow sorghum was significant (p ≤ 0.05) while the difference was not significant (p ≤ 0.05) between the white and yellow sorghum. It was also found that the three sorghum varieties are richer in potassium, zinc and sodium and low in the other mineral elements analyzed. The proximate analysis revealed that sorghum samples contain appreciable nutrient contents and vitamin analysis shows that red sorghum is nutritionally more valuable than the white and yellow sorghum.